The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1097/ico.0b013e318269ccd0
|View full text |Cite
|
Sign up to set email alerts
|

Metalloproteinases in Corneal Diseases

Abstract: Matrix metalloproteinases (MMPs) are zinc-dependent endopeptidases with the potential to degrade all types of extracellular matrix. The ADAM (a disintegrin and metalloproteinase) family of peptidases was recently identified as cleaving the extracellular domain of transmembrane proteins. This was termed ectodomain shedding. We investigated the MMP expression in patients with corneal diseases and the potential role of ADAMs in corneal pathophysiology. We detected upregulation of the active form of MMP-2 and MMP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 21 publications
1
39
0
1
Order By: Relevance
“…The ultrastructure studies have revealed altered lamellar collagen organisation, collagen fibril thinning, decreased epithelial hypoplasia, Bowman’s layer breaks and stromal thinning in the ectatic region of the cornea 23 24. Functional association between collagen degradation process (characteristic of ectasia) and inflammation has been reported 25. Other factors such as pregnancy and eye rubbing that serve as triggers for PLE also suggest a plausible inflammatory component to the pathogenesis of PLE.…”
Section: Discussionmentioning
confidence: 92%
“…The ultrastructure studies have revealed altered lamellar collagen organisation, collagen fibril thinning, decreased epithelial hypoplasia, Bowman’s layer breaks and stromal thinning in the ectatic region of the cornea 23 24. Functional association between collagen degradation process (characteristic of ectasia) and inflammation has been reported 25. Other factors such as pregnancy and eye rubbing that serve as triggers for PLE also suggest a plausible inflammatory component to the pathogenesis of PLE.…”
Section: Discussionmentioning
confidence: 92%
“…41 A study showed clusters of disrupted tight junction proteins, occludin and claudin, in conjunction with increased MMP-2 immunoreactivity in samples of superficial cornea epithelium obtained at night in Xenopus laevis. 42 While this mechanism for corneal epithelial desquamation has not been confirmed in human corneas, increased levels of MMP-2 and -9 have been found in cornea epithelium and tear fluid obtained from eyes with recurrent corneal epithelial erosion, 43,44 and increased proand active forms of MMP-9 have also been found in tears sampled from the closed eye during sleep when recurrent erosions typically occur while tear production and clearance are decreased. 45 There is mounting evidence that MMPs contribute to the altered cornea barrier function that is observed in dry eye.…”
mentioning
confidence: 99%
“…3 Cultured corneal fibroblasts produce MMP-1, -2, and -3, 24 and increased levels of these MMPs have been detected in melted corneal specimens from individuals with rheumatoid arthritis or ocular cicatricial pemphigoid 10 as well as in tear fluid of patients with corneal melting or recurrent corneal erosion. 25 MMP-1 is the collagenolytic enzyme that is largely responsible for the degradation of type I collagen, the major structural protein of the corneal stroma. The gelatinase MMP-2 degrades mostly type IV collagen and is thought to contribute to degradation of the epithelial basement membrane that promotes corneal ulceration.…”
Section: Discussionmentioning
confidence: 99%